A Distributed Election and Spanning Tree Algorithm Based on Depth First Search - Skyum, Sven (DAIMI Report Series, 1987)
The existence of an effective traversal algorithm for a class of graphs has proven useful in connection with election problems for those classes. In this paper we show how a general traversal algorithm, such as depth first search, can be turned into an effective election algorithm using modular techniques. The presented method also constructs a spanning tree for the graph.